Spiro‐OMeTAD:Sb2S3 Hole Transport Layer with Triple Functions of Overcoming Lithium Salt Aggregation, Long‐Term High Conductivity, and Defect Passivation for Perovskite Solar Cells. Issue 11 (15th September 2021) - Du, Qing; Shen, Zhitao; Chen, Chong; Li, Fumin; Jin, Mengqi; Li, Huilin; Dong, Chao; Zheng, Jihong; Ji, Mingxing; Wang, Mingtai
Abstract : The development of a hole transport layer (HTL) with persistent high conductivity, good moisture/oxygen barrier ability, and suitable passivation ability of perovskite defects is very important for achieving high power conversion efficiency (PCE) and long‐term stability of perovskite solar cells (PSCs). However, the state‐of‐the art HTL, lithium bis(trifluoromethanesulfonyl)‐imide (Li‐TFSI)‐doped 2, 2′, 7, 7′‐tetrakis‐( N, N ‐di‐ p ‐methoxyphenylamine)‐9, 9′‐spirobifluorene (spiro‐OMeTAD), does not have these abilities. Herein, the incorporation of antimony sulfide (Sb2 S3 ) nanoparticles as a multifunctional additive into spiro‐OMeTAD is demonstrated. The Sb2 S3 effectively improve the compactness of composite spiro‐OMeTAD:Sb2 S3 HTL by inhibiting the Li‐TFSI aggregation and effectively prevent the infiltration of moisture and oxygen into the perovskite layer, resulting in its high chemical stability. More importantly, Sb2 S3 not only improves the conductivity and hole mobility of the spiro‐OMeTAD:Sb2 S3 through the oxidation of spiro‐OMeTAD by Sb2 S3, but also makes the high conductivity more durable and stable in the atmospheric environment. In addition, Sb2 S3 also effectively passivates the perovskite defects and accelerates the charge transfer from perovskite layer to HTL. As a consequence, the optimized PSCs based on spiro‐OMeTAD:Sb2 S3 HTL exhibit a much higher PCE (22.13%) than that (19.29%) of the PSCs without Sb2 S3 and show a greatly improved stability. Abstract : Sb2 S3 as an additive in the spiro‐OMeTAD layer effectively inhibits Li‐TFSI aggregation through formed Li‐S bonds between Li‐TFSI and Sb2 S3, promotes the conductivity of the spiro‐OMeTAD layer through the oxidation of spiro‐OMeTAD by S atoms in Sb2 S3, and passivates the surface defects of the perovskite film significantly improving the efficiency and stability of perovskite solar cells.